Pengaruh Model Pembelajaran Inkuiri Terbimbing (Guided Inquiry) Berbasis Saintifik terhadap Kemampuan Berpikir Kritis Siswa - Fitria, Yulia; Safnowandi, Safnowandi; Fajri, Siti Rabiatul (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2022)
This study aims to determine the effect of the scientific-based guided inquiry learning model on the critical thinking skills of class X students. In this study there are 2 variables, namely the independent variable and the dependent variable, the independent variable is the guided inquiry learning model (Guided Inquiry). the dependent variable is students' critical thinking ability. The population of this study were students of class X MIA at MA Al-Ishlahul Ittihad Jabon Tentan Bagu Village, Pringgarata District, Central Lombok Regency. The selected sample is class X MIA with a total of 20 students. This study applies a quantitative approach with the Quasi Experiment method with a one group pre-test post-test design. The instrument used in the study was a written test in the form of 10 essay questions for the Pre-test 5 test questions and Post-test 5 test questions. The test questions were used to measure students' critical thinking skills on earthworm material. Based on the data analysis, the average pre-test was 63.75 which was included in the non-critical category and the post-test average was 81.75 which was included in the critical category. The data analysis technique in this study used a paired t test with the help of SPSS. Based on the results of the t-test, it was found that there was a significant difference between the results of the Pre-test and the Post-test. The results of the calculation of students' critical thinking ability data show that the value of sig = 0.000 0.05 then the HO hypothesis is rejected and Ha is accepted. Thus, it can be concluded that there is an influence of the guided inquiry learning model on the critical thinking skills of class X MIA students at MA Al-Ishlahul Ittihad Jabon Tentan Bagu Village, Pringgarata District, Central Lombok Regency.